Nursing care for the initiation of breastfeeding in the delivery room as perceived by mothers of newborns in primary care - Reyes López, Daniela Jeslín (2025)
Objective: To describe nursing care for the initiation of breastfeeding in the delivery room as perceived by mothers of newborns in primary care. Method: Qualitative-descriptive study involving 13 mothers of newborns, sample determined by data saturation and code redundancy techniques. The information was obtained using a semi-structured interview guide, validated by expert judgment and pilot testing, with the approval of the institutional ethics committee, then processed manually using content analysis. Results: Two categories emerged: nursing care for the establishment of breastfeeding in the delivery room and qualities of the nurse to ensure the establishment of breastfeeding. Conclusion: Primary care nurses promote breastfeeding in the delivery room through skin-to-skin contact for periods of 15 to 30 minutes; support, guidance, and counseling on breastfeeding, revealing non-compliance with current regulations and a lack of commitment to its promotion, support, and defense from the first hour of life.